Implementation of a Humanoid Robot as an Innovative Approach to Child Life Interventions in a Children’s Hospital: Lofty Goal or Tangible Reality? - Beran, Tanya N.; Pearson, Jacqueline Reynolds; Lashewicz, Bonnie (Frontiers in Psychology, 2021)
Introduction: This study reports the findings on how Child Life Specialists (CLSs) implemented an innovative approach to providing therapeutic support to pediatric patients. Methods: Part of a larger study that uncovered themes about CLSs experiences while working with MEDi®, this study reports the reflections that CLSs have about the process of implementation. Seven CLSs participated in semi-structured interviews. Content analysis was conducted on the responses, and three themes were generated. Results: The first was in regards to the adoption process whereby their challenges, successes, and surprises were revealed. Second, they explained how using MEDi® aligned with the roles and responsibilities of their profession. The third area of understanding was in their explanation of the friendly emotional impact MEDi® seems to have on the hospital environment. Conclusion: CLSs are encouraged to use the MEDi® robot to support children at the bedside.